Infrastructure Performance Indicators for Sea and Air Transportation Sectors in Indonesia - Ayomi Dita Rarasati; Yusuf Latief; Isti Surjandari Prajitno; Jade Sjafrecia Petrociany; Perdana Miraj (Jurnal Transportasi: Sistem, Material, dan Infrastruktur, 2018)
This research is conducted to assess infrastructure performance in Indonesian sea and air transportation sector. The performances are assessed based on indicators which are identified within the initiation of this research. There are seven indicators identified which are the number of infrastructure existed; passengers demand per year; cargo demand per year; local government revenue; passenger growth per year; cargo growth per year; and the city population. The aim of this paper is to present the most significant indicators which are affecting the infrastructure performance. Based on a descriptive analysis, it can be showed that these indicators affect Indonesian sea and air transportation performance. Three perspectives from central government, local government and academics were further elaborated in this paper. From the government point of view, the most important indicator of sea and air transportation performance are the numbers of ports or airports and passenger growth per year.